Roles of the RON3 C-terminal fragment in erythrocyte invasion and blood-stage parasite proliferation in Plasmodium falciparum - Ito, Daisuke; Kondo, Yoko; Takashima, Eizo; Iriko, Hideyuki; Thongkukiatkul, Amporn; Torii, Motomi; Otsuki, Hitoshi (Frontiers in Cellular and Infection Microbiology, 2023)
Plasmodium species cause malaria, and in the instance of Plasmodium falciparum is responsible for a societal burden of over 600,000 deaths annually. The symptoms and pathology of malaria are due to intraerythocytic parasites. Erythrocyte invasion is mediated by the parasite merozoite stage, and is accompanied by the formation of a parasitophorous vacuolar membrane (PVM), within which the parasite develops. The merozoite apical rhoptry organelle contains various proteins that contribute to erythrocyte attachment and invasion. RON3, a rhoptry bulb membrane protein, undergoes protein processing and is discharged into the PVM during invasion. RON3-deficient parasites fail to develop beyond the intraerythrocytic ring stage, and protein export into erythrocytes by the Plasmodium translocon of exported proteins (PTEX) apparatus is abrogated, as well as glucose uptake into parasites. It is known that truncated N- and C-terminal RON3 fragments are present in rhoptries, but it is unclear which RON3 fragments contribute to protein export by PTEX and glucose uptake through the PVM. To investigate and distinguish the roles of the RON3 C-terminal fragment at distinct developmental stages, we used a C-terminus tag for conditional and post-translational control. We demonstrated that RON3 is essential for blood-stage parasite survival, and knockdown of RON3 C-terminal fragment expression from the early schizont stage induces a defect in erythrocyte invasion and the subsequent development of ring stage parasites. Protein processing of full-length RON3 was partially inhibited in the schizont stage, and the RON3 C-terminal fragment was abolished in subsequent ring-stage parasites compared to the RON3 N-terminal fragment. Protein export and glucose uptake were abrogated specifically in the late ring stage. Plasmodial surface anion channel (PSAC) activity was partially retained, facilitating small molecule traffic across the erythrocyte membrane. The knockdown of the RON3 C-terminal fragment after erythrocyte invasion did not alter parasite growth. These data suggest that the RON3 C-terminal fragment participates in erythrocyte invasion and serves an essential role in the progression of ring-stage parasite growth by the establishment of the nutrient-permeable channel in the PVM, accompanying the transport of ring-stage parasite protein from the plasma membrane to the PVM.